2010
DOI: 10.3390/molecules15117715
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microwave-Assisted and Conventional Hydrodistillation in the Extraction of Essential Oils from Mango (Mangifera indica L.) Flowers

Abstract: Microwave-assisted hydrodistillation (MAHD) is an advanced hydrodistillation (HD) technique, in which a microwave oven is used in the extraction process. MAHD and HD methods have been compared and evaluated for their effectiveness in the isolation of essential oils from fresh mango (Mangifera indica L.) flowers. MAHD offers important advantages over HD in terms of energy savings and extraction time (75 min against 4 h). The composition of the extracted essential oils was investigated by GC-FID and GC-MS. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 29 publications
5
45
0
3
Order By: Relevance
“…Novel microwave‐assisted extraction (MAE) (Kaufmann and Christen 2002) methods such as microwave‐assisted hydrodistillation (MAHD) (Golmakani and Rezaei 2008a,b; Wang et al. 2010) and solvent‐free microwave extraction (SFME) (Filly et al. 2014) have proven to be fast and efficient methods for extracting EOs from medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Novel microwave‐assisted extraction (MAE) (Kaufmann and Christen 2002) methods such as microwave‐assisted hydrodistillation (MAHD) (Golmakani and Rezaei 2008a,b; Wang et al. 2010) and solvent‐free microwave extraction (SFME) (Filly et al. 2014) have proven to be fast and efficient methods for extracting EOs from medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, la HD es un método sencillo, reproducible, económico y, sobre todo, ampliamente utilizado en la industria [6,26,27,36,37].…”
Section: Discussionunclassified
“…Los rendimientos en la extracción se evaluaron por triplicado a tiempos de 20, 30, 40, 50, 60, 90, 120 y 180 min, operando siempre bajo las mismas condiciones [4,5,26,27], según la ecuación (1):…”
Section: Procedimientos De Extracción Del Aeunclassified
“…Likewise, reference [6] concluded that microwave steam diffusion (MSDf) for extraction of essential oil from orange peel is clearly advantageous in term of energy and time; the extraction time using MSDf method of 12 min versus 40 min of conventional steam diffusion (SDf) as well as the required energy to perform the two extraction methods are 300 kWh kg -1 essential oil and 120 kWh kg -1 essential oil for SDf and MSDf, respectively. On the other hand, no significant differences in chemical composition were found for the obtained essential oils by microwave steam distillation versus by steam distillation [7], and also by MAHD versus by HD [9]. Therefore, it is important to conduct further studies on the P. cubeba essential oil extraction using microwave as power source in order to improve the efficiency of the process.…”
Section: Introductionmentioning
confidence: 98%